Tokyo tarareba girls. 8 - Higashimura, Akiko (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
"At last, Rinko's found it--the happy, comfortable relationship she's dreamt of. She and Hayasaka-san have moved into an apartment together, and her best friends have wished her well. Everything is going smoothly...until those same best friends show up breathless at her doorstep with the biggest four-alarmer yet: Key's gone missing, and Rinko may be the only one who can find him and bring him back. But the rescue may come at the cost of everything she thought she wanted..."--Provided by publisher.